CD28 affects the earliest signaling events generated by TCR engagement. - Tuosto, L; Acuto, O (1998)
The efficiency and magnitude of T cell responses are influenced by ligation of the co-stimulatory receptor CD28 by B7 molecules expressed on antigen-presenting cells (APC). In contrast to most previous studies in which agonistic anti-TCR/CD3 and anti-CD28 antibodies were employed, here we have investigated the contribution of CD28 to T cell activation under physiological conditions of antigen presentation. Jurkat T cells and primary T cells from TCR-transgenic mice stimulated with superantigen and antigen, respectively, presented by B7-expressing APC were utilized. In both systems we show that inhibiting CD28/B7 interaction resulted in impaired TCR-induced tyrosine phosphorylation of the signal-transducing zeta chain and ZAP-70. Consistent with a blockade of TCR-proximal signaling events, Jurkat cells stimulated in the absence of CD28 ligation were found to have strongly diminished tyrosine phosphorylation of cellular substrates and downstream signaling pathways such as Ca2+/calcineurin, ERK/MAPK and JNK. Our results provide evidence for a role of CD28 in enhancing TCR signaling capacity during the earliest stages of T cell:APC interaction.